The Effect of Filler Orientation and Distribution on the Electrical and Mechanical Properties of Graphene Based Polymer Nanocomposites - Rajamani, Praveen Kannan; Boros, Róbert (Acta Technica Jaurinensis, 2018)
The aim of my proposed study is to develop an alternative production technique of graphene via in-situ exfoliation of graphite in the hosting polymer matrix. The production process is carried out by an alternative top-down production technique for graphene-based polymer nanocomposites called ‘pressing and folding’ (P&F), via in situ exfoliation of expanded graphite (EG) inside the hosting linear low-density polyethylene (LLDPE) matrix. In this way, the properties of the samples containing different wt % of EG is studied as a function of P&F cycles, corresponding to EG exfoliation and distribution throughout the matrix volume. The results confirm that the EG particles was exfoliated completely and increasingly distributed in LLDPE with the number of cycles, and mainly oriented on the plane of the samples. This find was confirmed by a low in-plane resistivity was found for samples prepared between 50 and 150 cycles.